PENGEMBANGAN GAME EDUKASI BERBANTU EDUCAPLAY PADA MATERI LAPISAN BUMI KELAS V SDN 151 PEKANBARU - Sonia Firda Zalianti; Dea Mustika (STKIP Subang, 2026)
This study aims to develop, determine the validity of, and identify user responses to an Educaplay-assisted educational game on Earth's Layers for fifth-grade students. The study was motivated by low student interest and limited interactive media in IPAS learning at SDN 151 Pekanbaru, especially for the abstract concepts of lithosphere, hydrosphere, and atmosphere. The study used Research and Development (R&D) with the ADDIE model, limited to Analysis, Design, and Development. Analysis covered teacher needs, student needs, and curriculum. Design produced Map Quiz and Quiz activities on Educaplay, followed by self-evaluation with a score of 100%. Data were collected through interviews, observation, documentation, and questionnaires and analyzed qualitatively and quantitatively. The product was validated by six experts (two media, two language, and two content experts) and responded to by one teacher and ten fifth-grade students. Results showed product validity of 96.22% (Very Valid), consisting of 98% media, 93.33% language, and 97.33% content. Teacher response was 97.33% and student response was 100%, with an overall average of 98.67% (Very Good). Thus, the Educaplay-assisted educational game is valid and well received as an alternative learning medium for Earth's Layers in elementary school.